Synergistic Single-Atom and Clustered Cobalt Sites on N/S Co-Doped Defect Nano-Carbon for Efficient H2O2 Electrosynthesis - Huang, Yuzhong; Zhang, Chang; Wang, Xingyu; Wu, Yuji; Lv, Jun; Zhang, Jian; Shen, Wangqiang; Lu, Xing (Nano-Micro Letters, 2025)
Non-noble-based single atomic catalysts have exhibited significant potential in electrochemical production of H2O2 via two-electron oxygen reduction reactions (2e− ORR). However, constructing highly efficient and acid-resistant catalysts remains a challenge but significant. In this work, fullerene (C60) with abundant pentagonal inherent defects was employed as a carbon substrate to synthesize defect-rich nanocarbon electrocatalysts doped with NSCo single atoms and accompanied by metallic Co nanoparticles (CoSA/CoNP-NSDNC) for the first time. The electrochemical experiments demonstrate that the active sites of CoSA/CoNP-NSDNC are formed through the synergistic interaction between NSCo single atoms and Co nanoparticle clusters embedded within the carbon framework. The obtained CoSA/CoNP-NSDNC catalyst exhibits an onset potential as 0.72 V versus RHE and achieves up to 90% H2O2 selectivity over a wide potential range of 500 mV. Moreover, the as-obtained CoSA/CoNP-NSDNC configured as the cathode in a self-assembled flow cell under acidic conditions achieves a high H2O2 production rate of 4206.96 mmol gcat⁻1 h⁻1 with a Faraday efficiency of ∼ 95% and exhibit ultra fast degradation of organic pollutants. This work focuses on the synergistic effect of non-noble metal nanoparticles, metal single-atom sites, and topological defects on the 2e− ORR process, which provides a new direction for designing carbon-based catalysts for efficient H2O2 electrosynthesis. Highlights: 1 Defect-rich nanocarbon catalyst (CoSA/CoNP-NSDNC) synthesized using NSCo single atoms and Co nanoparticle clusters on fullerene-derived carbon framework, enabling efficient H2O2 electrosynthesis. 2 The CoSA/CoNP-NSDNC catalyst exhibits high H2O2 selectivity ( 90%) over a wide potential range with an onset potential of 0.72 V versus RHE, achieving Faraday efficiency close to 95% in acidic conditions. 3 Demonstrates potential for environmental applications, achieving high H2O2 production (4206.96 mmol g−1 h−1) in a flow cell setup, along with efficient degradation of organic pollutants in Fenton-like reactions.